Pengetahuan Berkorelasi Positif dengan Perilaku Pencegahan Covid–19 pada Mahasiswa di Gorontalo - Firdausi Ramadhani; Nuryani Nuryani (Sarana Ilmu Indonesia (salnesia), 2020)
Covid-19 is a disease caused by a new type of coronavirus that has never been identified as attacking humans before. Knowledge and attitudes are expected to have correlated with Covid-19 prevention behavior. The study aimed to determine the association between knowledge and attitude with Covid-19 prevention behavior among college students in Gorontalo. This study was a quantitative study with a correlation analytic design. A sample of 187 subjects was taken randomly through the google form application which was distributed via WhatsApp to students in Gorontalo Province. Measurement variables of knowledge, attitudes and behavior to prevent Covid-19 were used a questionnaire with a Likert and Guttman scale. Data were analyzed using the Spearman correlation analysis. The results were showed that the subjects more female (79.7%) than male (20.3%). Many of the scientific fields were in the health sector (77.0%), while the domicile was more from outside the district and city of Gorontalo (52.9%). The average knowledge score was 82.47 ± 14.10, attitude score 80.48 ± 7.82 and Covid-19 prevention behavior score 83.36 ± 17.89. Correlation analysis showed that there was an association between knowledge and Covid-19 prevention behavior (r = 0.178; p-value = 0.015) with the degree of weak relationship and there was no association between attitudes and Covid-19 prevention behavior in students (r = -0.012; p-value = 0.874). There was a relationship between knowledge and Covid-19 prevention behavior.